1997
DOI: 10.1046/j.1365-3156.1997.d01-298.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria-related beliefs and behaviour in southern Ghana: implications for treatment, prevention and control

Abstract: A research infrastructure was established in two ecological zones in southern Ghana to study the variables of malaria transmission and provide information to support the country's Malaria Action Plan (MAP) launched in 1992. Residents' beliefs and practices about causes, recognition, treatment and prevention of malaria were explored in two ecological zones in southern Ghana using epidemiological and social research methods. In both communities females constituted more than 80% of caretakers of children 1-9 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
111
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 0 publications
26
111
1
1
Order By: Relevance
“…This observation is similar with other studies done in Tanzania [20][21][22], Eritrea [23], and Sudan [24]. None of the pregnant women indicated that they have visited traditional healers as reported in other studies [25][26][27] or village health team (VHT) member to seek for treatment. Also, none of the respondent mentioned that they use herbs to treat malaria as reported in other studies [21,27].…”
Section: Discussionsupporting
confidence: 90%
“…This observation is similar with other studies done in Tanzania [20][21][22], Eritrea [23], and Sudan [24]. None of the pregnant women indicated that they have visited traditional healers as reported in other studies [25][26][27] or village health team (VHT) member to seek for treatment. Also, none of the respondent mentioned that they use herbs to treat malaria as reported in other studies [21,27].…”
Section: Discussionsupporting
confidence: 90%
“…All parasitological and entomological data was analyzed with the statistical package for social sciences (SPSS) [8]. Proportions were compared using the chi-square or t-test.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]13,[18][19][20][21][22] One concern about the use of interview surveys to estimate morbidity and drug use is their amenability to bias. 23,24 How well does the occurrence of illness episodes and drug use reported in questionnaire surveys correspond to the occurrence of such episodes measured using biomedical criteria?…”
Section: Discussionmentioning
confidence: 99%